Вторичные энергетические ресурсы - резерв экономии - Букато В. М. Виктор Михайлович; Ганжин А. А. Александр Антонович; Козлов А. И. Анатолий Иванович; Мигуцкий Е. Г.; Худолей Д. А. (Минск, Беларусь, 1985)
Авт. указаны на обороте тит. л.